Intraoperative recurrent laryngeal nerve monitoring: a useful method for patients with esophageal cancer. Issue 5 (1st July 2014) - Zhong, D.; Zhou, Y.; Li, Y.; Wang, Y.; Zhou, W.; Cheng, Q.; Chen, L.; Zhao, J.; Li, X.; Yan, X.
Summary: It is well accepted that recurrent laryngeal nerve paralysis is a severe complication of esophagectomy or lymphadenectomy performed adjacent to the recurrent laryngeal nerves. Herein, determination of the effectiveness of implementing continuous recurrent laryngeal nerve monitoring to reduce the incidence of recurrent laryngeal nerve paralysis after esophagectomy was sought. A total of 115 patients diagnosed with esophageal cancer were enrolled in the thoracic section of the T angdu H ospital of the F ourth M ilitary M edical U niversity from A pril 2008 to A pril 2009. Clinical parameters of patients, the morbidity, and the mortality following esophageal resection were recorded and compared. After the surgery, a 2-year follow up was completed. It was found that recurrent laryngeal nerve paralysis and postoperative pneumonia were more frequently diagnosed in the patients that did not receive continuous recurrent laryngeal nerve monitoring (6/61 vs. 0/54). Furthermore, positive mediastinal lymph nodes ( P = 0.015), total mediastinal lymph nodes ( P < 0.001), positive total lymph nodes ( P = 0.027), and total lymph nodes ( P < 0.001) were more often surgically removed in the patients with continuous recurrent laryngeal nerve monitoring. These patients also had a higher 2-year survival rate ( P = 0.038) after surgery. It was concluded that continuous intraoperative recurrent laryngeal nerve monitoring is technically safe and effectively identifies the recurrent laryngeal nerves. This may be a helpful method for decreasing the incidence of recurrent laryngeal nerve paralysis and postoperative pneumonia, and for improving the efficiency of lymphadenectomy.